Understanding Suicide Cases in Nepal: A Comprehensive Analysis of Personality Traits - Neupane, Alaka; Baral, Bharat Raj (Baneshwor Campus Journal of Academia, 2024)
Understanding the intricate relationship between personality traits and suicidal tendencies is crucial for effective suicide prevention strategies. This paper delves into the influence of the Big Five personality traits - Openness, Conscientiousness, Extraversion, Agreeableness, and Neuroticism (OCEAN) - on susceptibility to suicidal thoughts and behaviors. Through a comprehensive review of the literature and analysis of relevant cases, it explores how various personality traits intersect with suicidal ideation. Findings reveal that high neuroticism, characterized by emotional instability and negative affectivity, significantly correlates with suicidal intentions. Additionally, lower levels of agreeableness are associated with elevated suicide rates, suggesting a lack of empathy and cooperation may contribute to suicidal thinking. The paper underscores the importance of considering personality factors in suicide risk assessment and intervention strategies. By recognizing the role of personality traits in shaping individuals' responses to distress, tailored interventions can be developed to mitigate suicide risk and promote mental well-being.